A review of methods, applications and limitations for incorporating fluid flow in the discrete element method - Wang, Tuo; Zhang, Fengshou; Furtney, Jason; Damjanac, Branko (Journal of Rock Mechanics and Geotechnical Engineering, 2022)
The past decade has witnessed the substantial growth in research interests and progress on the subject of coupled hydro-mechanical processes in rocks and soils, driven mainly by the surge of research in unconventional hydrocarbon reservoirs and associated hazards. Many coupling techniques have been developed to include the effects of fluid flow in the discrete element method (DEM), and the techniques have been applied to a variety of geomechanical problems. Although these coupling methods have been successfully applied in various engineering fields, no single fluid/DEM coupling method is universal due to the complexity of engineering problems and the limitations of the numerical methods. For researchers and engineers, the key to solve a specific problem is to select the most appropriate fluid/DEM coupling method among these modeling technologies. The purpose of this paper is to give a comprehensive review of fluid flow/DEM coupling methods and relevant research. Given their importance, the availability or unavailability of best practice guidelines is outlined. The theoretical background and current status of DEM are introduced first, and the principles, applications, and advantages and disadvantages of different fluid flow/DEM coupling methods are discussed. Finally, a summary with speculation on future development trends is given.